Welfare Measurement and Poverty Targeting Based on Participatory Wealth Rankings - Martin Wiegand (Tinbergen Institute, 2020)
Participatory wealth rankings (PWRs) present an inclusive and inexpensive targeting method to identify poor households. They tend to be well received by participants but point to a systematically different understanding of welfare than implied by consumption-based rankings. This suggests that PWRs could be used as the basis for alternative welfare measures that aim to reflect local perceptions of poverty. This paper demonstrates how such a measure can be constructed, using data from a field experiment on poverty targeting in Indonesia. It then explores the potential impact of using this welfare measure as targeting goal on participants' and village leaders' satisfaction. I find that higher targeting accuracy—using the PWR-based measure as benchmark—increases satisfaction with the program. However, after controlling for targeting accuracy, the PWR does not lead to discernibly higher satisfaction than a proxy means targeting mechanism. The PWRs thus seem to be appreciated for their resulting allocations rather than valued intrinsically. I also find that targeting accuracy explains satisfaction outcomes better when it is measured against PWR-based welfare rather than predicted consumption. This holds true even for communities where no actual PWRs had been conducted. The results suggest that the information contained in PWRs can be used as a meaningful basis for targeting and poverty measurement.
Keywords: C8; D63; I32; I38; O1; 330; poverty; targeting preferences; welfare measures; participatory wealth ranking